Genital ulceration does not increase HIV-1 shedding in cervical or vaginal secretions of women taking antiretroviral therapy. Issue 2 (27th October 2010) - Graham, Susan M; Masese, Linnet; Gitau, Ruth; Richardson, Barbra A; Mandaliya, Kishor; Peshu, Norbert; Jaoko, Walter; Ndinya-Achola, Jeckoniah; Overbaugh, Julie; McClelland, R Scott
Abstract : Objectives: Genital ulcer disease (GUD) is associated with increased HIV-1-RNA shedding in antiretroviral therapy (ART)-naive women. The effect of GUD on HIV-1 shedding among ART-treated women is not known. The objective of this study was to test the hypothesis that genital ulcerations increase genital HIV-1-RNA shedding in women receiving ART. Methods: Eligible women initiated ART and attended monthly visits with inspection for genital lesions and collection of genital swabs. GUD cases diagnosed after 2 months or more on ART were included for analysis and served as their own controls. HIV-1 RNA was quantitated in specimens collected before, during and after GUD for all cases. The lower limit of quantitation was 100 HIV-1-RNA copies/swab. Using the pre-GUD visit as the reference, the detection of genital HIV-1 RNA before versus during and after GUD episodes was compared. Results: 36 women had GUD episodes after ART initiation. HIV-1 RNA was detected before, during and after GUD in cervical secretions from four (11%), one (3%) and six (17%) women, respectively, and in vaginal secretions from three (8%), four (11%) and four (11%) women, respectively. After adjustment for time on ART, there was no difference in the detection of cervical HIV-1 RNA before versus during GUD (adjusted OR 0.22, 95% CI 0.04 to 1.23). Likewise, GUD did not increase HIV-1 detection in vaginal secretions (adjusted OR 1.32, 95% CI 0.29 to 5.92). Conclusions: GUD did not significantly increase cervical or vaginal HIV-1 shedding. The results suggest that ART maintains its effectiveness for genital HIV-1 suppression despite GUD episodes.